La comunicación no verbal en el nado sincronizado (2004)
ABSTRACT: In sports specialized communication and in instrumental music, non-verbal communication constitutes an aspect of vital importance in the exchange of information, especially if it is considered that in general human communication this type of behavior constitutes nearly 65% of the process (Pei, 1949), moreover, it is an aspect that has received relatively little attention by linguistic studies and mainly by terminological studies. Starting with a systematized study of a non-verbal communication in a determined area of knowledge, we propose a definition, dynamic representation and further storage of the specific concepts thereupon generated.